2013
DOI: 10.2466/06.10.pr0.113x27z2
|View full text |Cite
|
Sign up to set email alerts
|

College Residential Sleep Environment

Abstract: College students regularly report increased sleep disturbances as well as concomitant reductions in performance (e.g., academic grades) upon entering college. Sleep hygiene refers to healthy sleep practices that are commonly used as first interventions in sleep disturbances. One widely used practice of this sort involves arranging the sleep environment to minimize disturbances from excessive noise and light at bedtime. Communal sleep situations such as those in college residence halls do not easily support thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…Before lockdown, scores are similar for each variable, however, lockdown only caused significant changes to those living with family. Living with other students during the academic year, such as at university residences or shared flats, had an influence on sleep quality [ 45 ]. All students living in university residences or rented flats had to return to their family homes and this could have improved sleep quality, preventing any significant differences in the scores during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Before lockdown, scores are similar for each variable, however, lockdown only caused significant changes to those living with family. Living with other students during the academic year, such as at university residences or shared flats, had an influence on sleep quality [ 45 ]. All students living in university residences or rented flats had to return to their family homes and this could have improved sleep quality, preventing any significant differences in the scores during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The second theme that became apparent to researchers was that uncomfortable dorm environments led to sleep disturbances due to factors such as excessive noise and light at bedtime. Previous studies pointed out that an adequate sleep environment is important to obtain an appropriate quality and quantity of sleep (Caddick, Gregory, Arsintescu, & Flynn-Evans, 2018;Sexton-Radek, & Hartley 2013).…”
Section: Table 1 Participant's Demographicsmentioning
confidence: 99%
“…Sleeping in residence can be a challenging experience for students because of the unique environment, roommates' different habits, and uncomfortable bedroom temperature (Sexton-Radek & Hartley, 2013). A study showed sleep difficulty was one of the predictors of stress for students who live in residence (Dusselier et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a critical life period to both adopt and discontinue behaviors and self-care activities related to health (Viner et al, 2012). Sleep is one such self-care challenges and poor sleep is a potential obstacle to success for HE students (Orzech, Salafsky, & Hamilton, 2011;Sexton-Radek & Hartley, 2013;Gaultney, 2016). A study of health-risk behaviors among post-secondary students across eight Canadian HE institutions showed that 75.6% of students did not get adequate sleep (Kwan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%